Paroxysmal hypnogenic dyskinesia is associated with mutations in the PRRT2 gene - Liu, Xiao-Rong (Neurol Genet, 2016)
OBJECTIVE: To explore the potential causative genes of paroxysmal hypnogenic dyskinesia (PHD), which was initially considered a subtype of paroxysmal dyskinesia and has been recently considered a form of nocturnal frontal lobe epilepsy (NFLE). METHODS: Eleven patients with PHD were recruited. Mutations in proline-rich region transmembrane protein-2 (PRRT2), myofibrillogenesis regulator 1 (MR-1), solute carrier family 2, member 1 (SLC2A1), calcium-activated potassium channel alpha subunit (KCNMA1), cholinergic receptor, nicotinic, alpha 4 (CHRNA4), cholinergic receptor, nicotinic, beta 2 (CHRNB2), cholinergic receptor, nicotinic, alpha 2 (CHRNA2), and potassium channel subfamily T member 1 (KCNT1) were screened by direct sequencing. RESULTS: Two PRRT2 mutations were identified in patients with typical PHD. A mutation of c.649dupC (p.Arg217ProfsX8) was identified in a patient with PHD and his father who was diagnosed with paroxysmal kinesigenic dyskinesia. An additional mutation of c.640G>C (p.Ala214Pro) was identified in a sporadic patient and his asymptomatic mother. No mutations were found in the other screened genes. CONCLUSIONS: The present study identified PRRT2 mutations in PHD, extending the phenotypic spectrum of PRRT2 and supporting the classification of PHD as a subtype of paroxysmal dyskinesia but not NFLE. Based on the results of this study, screening for the PRRT2 mutation is recommended in patients with PHD.